Pengaruh Globalisasi terhadap Identitas Budaya Lokal dan Dinamika Sosial Masyarakat di Dieng Wonosobo - Nuryanti Nuryanti; Sofiyatul Mukaromah; Nurul Mubin (CV. KAMPUS AKADEMIK PUBLISING, 2024)
This article aims to understand the impact of globalization on local cultural identity and social dynamics, particularly in the Dieng region, Wonosobo. Culture is a fundamental concept in human life, encompassing values, beliefs, norms, and traditions passed down through generations. In the modern context, globalization poses a significant challenge to the preservation of local culture, as technological advancements and cross-cultural exchanges accelerate the spread of foreign cultures. The effects of globalization influence local cultural identity and social dynamics, often forcing local cultures to compete with global ones. This article examines three important aspects: the background of cultural emergence, the function of culture in social life, and the dynamics of culture in the era of globalization. Descriptive and qualitative methods are used to explain cultural changes and challenges in the modern era. The research results indicate that, while globalization brings opportunities, it also poses risks of losing local cultural identity. Therefore, strategic efforts are needed to preserve local culture amidst the tide of globalization